Leading school-age educare in Sweden: Regimes of practices and principals’ subjectivities - Holmberg, Linnéa; Kane, Eva (Frontiers in Education, 2025)
How do primary school principals responsible for Swedish school-age educare (SAEC) describe their work? By understanding the principals’ practise as a site of power relations within regimes of practises and, through this, exploring principal subjectivities, it becomes possible to reveal which types of educational leadership for school-age educare are normalised and made possible. In an analysis based on answers from primary school principals in a qualitative survey, a discursive production of a nebulous leadership subject emerges; a bland and nebulous leader is enabled and, at the same time, constrained by the power relations within the regime of practises. This leadership terrain is not easy to navigate and appears to be guided by the notion that good enough is enough. This leadership style is changeable as well as varied, and at the same time, apparently marked by an unwillingness to shoulder all the responsibility for SAEC, and consequently, seeks support in different ways from different directions, transforming responsibility into a collective project driven by joint forces. It is also leadership that constantly needs to adapt its commitments to the needs of others, which in turn leads to a reactive rather than a proactive leadership style. Finally, it is leadership that appears legitimate, even though adequate knowledge about SAEC sometimes appears to be lacking, to some extent, pointing towards an abdicated leadership. For a different type of educational leader for school-age educare to emerge, a changed regime of practises is required, allowing the primary school principals to perform their leadership in ways that today do not appear possible.